On cognitive ecology and the environmental factors that promote Alzheimer disease: lessons from Octodon degus (Rodentia: Octodontidae). Issue 1 (December 2016) - Rivera, Daniela; Inestrosa, Nibaldo; Bozinovic, Francisco
Abstract Cognitive ecologist posits that the more efficiently an animal uses information from the biotic and abiotic environment, the more adaptive are its cognitive abilities. Nevertheless, this approach does not test for natural neurodegenerative processes under field or experimental conditions, which may recover animals information processing and decision making and may explain, mechanistically, maladaptive behaviors. Here, we call for integrative approaches to explain the relationship between ultimate and proximate mechanisms behind social behavior. We highlight the importance of using the endemic caviomorph rodentOctodon degus as a valuable natural model for mechanistic studies of social behavior and to explain how physical environments can shape social experiences that might influence impaired cognitive abilities and the onset and progression of neurodegenerative disorders such as Alzheimer disease. We consequently suggest neuroecological approaches to examine how key elements of the environment may affect neural and cognitive mechanisms associated with learning, memory processes and brain structures involved in social behavior. We propose the following three core objectives of a program comprising interdisciplinary research inO. degus, namely: (1) to determine whether diet types provided after weaning can lead to cognitive impairment associated with spatial memory, learning and predisposing to develop Alzheimer disease in younger ages; (2) to examine if early life social experience has long term effects on behavior and cognitive responses and risk for development Alzheimer disease in later life and (3) To determine if an increase of social interactions in adult degu reared in different degree of social stressful conditions alter their behavior and cognitive responses.